Product complexity in the adoption of user-customized systems - Benedikt Gamharter; Heli Koski; Tobias Kretschmer (The Research Institute of the Finnish Economy (ETLA), 2009)
We study firm-level adoption of packaged software products of almost 4,000 UK sites between 2000 and 2003. We consider all software used in a firm as its software product and categorize it into related, but distinct subsystems: the core subsystem (Operating Systems), and Desktop and Enterprise Applications, which we define as peripheral subsystems. Adoption is studied across those subsystems. We find that larger firms tend to adopt and switch subsystems more often. We further consider three factors that may affect the adoption decision: product complexity, architectural innovation and competency scale. The complexity of existing peripheral sub-systems hinders switching with the exception of the UNIX operating system that becomes a more likely choice for firms with complex IT systems. UNIX OS is also adopted more often by firms with higher IT competency. Further, earlier generational expansion of peripheral subsystems generally decreases the likelihood of further adoptions. Architectural changes hinders adoption of some, but not all software applications.
Keywords: L15; L86; O33; 330; Software; diffusion; innovation; system products; Software; Betriebliches Informationssystem; Innovationsdiffusion; Produktdifferenzierung; Großbritannien